2023
DOI: 10.1007/s12144-023-04389-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of goal orientation on online learning: A meta-analysis of differences in Korea and US

Abstract: This meta-analysis examines the correlation between goal orientation and related variables in online learning to examine the influence of individual goal orientation on online learning as well as the differences arising from diverse cultural backgrounds. The study analyzed 27 papers from 2000 to 2022, comprising 8 US and 19 Korean studies. The average effect size of goal orientation and related variables, such as learning satisfaction, self-efficacy, and task value, were also analyzed. In addition, moderating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Research has shown that distance learning can be as effective as traditional classroom-based learning, with students achieving similar learning outcomes [27], [28]. However, it is important to note that both hybrid and distance learning require a significant amount of self-discipline and motivation from students, as they are largely responsible for managing their own learning and staying on track with their coursework [29]- [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that distance learning can be as effective as traditional classroom-based learning, with students achieving similar learning outcomes [27], [28]. However, it is important to note that both hybrid and distance learning require a significant amount of self-discipline and motivation from students, as they are largely responsible for managing their own learning and staying on track with their coursework [29]- [33].…”
Section: Literature Reviewmentioning
confidence: 99%